3D POSS cages decorated 2D graphenic sheets: A versatile platform for silicon-carbonaceous nano-additives design. (15th February 2021) - Lungu, A.; Cernencu, A.I.; Vlasceanu, G.M.; Florea, N.M.; Ionita, M.; Iovu, H.
Abstract: This review paper provides the basic knowledge for fundamental understanding of the covalent intercalation of graphenic materials with polyhedral oligosilsesquioxanes (POSS) along with the latest progress in designing of silicon-carbonaceous nano-additives. Therefore, the aim of this work was to review the effect of the addition of 3D POSS nano-building blocks anchored onto 2D graphenic materials nano-sheets within various polymeric matrices to acquire high-performance nanocomposites in terms of essential features such as thermal, mechanical, rheological, dielectrical, flame-retardant, barrier or electrochemical sensing properties. Recent developments highlighting the usage of such complex hybrid nano-additives in polymeric materials in the last ten years were emphasized. Breakthrough in compositing graphenic strains (thinnest and most stable materials) with POSS (smallest silica particles one can attain) eases off some particular limitations and unlocks the advance of select technologies. Graphical abstract: Image 1